Association of nursing hours with cognitive function, balance, and dependency level of stroke patients. Issue 3 (27th October 2022) - Lee, Haneul; Lee, Kyounga; Lee, Seon‐Heui
Abstract: Aims: To examine the association of nursing hours given to patients with stroke with clinical characteristics to predict the nursing care needs. Design: Twenty‐four‐hour observational study Methods: Nursing hours per patient day (NHPPD) of 171 stroke patients were measured by 146 nursing personnel who worked on the day of the observation. Cognitive function, balance ability and dependency level were assessed using the Korean version of the Mini‐Mental State Examination (K‐MMSE), the Korean version of the Berg Balance Scale (K‐BBS) and the Korean version of the Modified Barthel Index (K‐MBI), respectively. Results: The NHPPD were moderately correlated with K‐MMSE ( r = −.450), K‐BBS ( r = −.529) and K‐MBI ( r = −.549). The worse the cognitive function, balance ability and dependency level, the more were the nursing hours given to the patients. Therefore, these factors can be considered to be factors that predict nursing care needs for patients with stroke.